2019
DOI: 10.1038/s41598-019-50057-8
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced changes of the subretinal space of the temporal retina observed via optical coherence tomography

Abstract: Photoreceptor function is impaired in many retinal diseases like age-related macular degeneration. Currently, assessment of the photoreceptor function for the early diagnosis and monitoring of these diseases is either subjective, as in visual field testing, requires contact with the eye, like in electroretinography, or relies on research prototypes with acquisition speeds unattained by conventional imaging systems. We developed an objective, noncontact method to monitor photoreceptor function using a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Moreover, advanced ORG processing algorithms allow the mapping of various functional activities over morphological images. While the implementation of OCT-ORG in clinics is still at an early stage, recent studies demonstrated the feasibility of ORG measurement in human subjects ( 25 , 31 , 32 , 36 , 37 , 54 , 57 , 69 , 70 , 102 , 105 ). To facilitate clinical transition, it would be necessary to refine experimental procedures and shorten the examination time, including the light/dark adaptation to reduce the subject's burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, advanced ORG processing algorithms allow the mapping of various functional activities over morphological images. While the implementation of OCT-ORG in clinics is still at an early stage, recent studies demonstrated the feasibility of ORG measurement in human subjects ( 25 , 31 , 32 , 36 , 37 , 54 , 57 , 69 , 70 , 102 , 105 ). To facilitate clinical transition, it would be necessary to refine experimental procedures and shorten the examination time, including the light/dark adaptation to reduce the subject's burden.…”
Section: Discussionmentioning
confidence: 99%
“…However, human study has sometimes shown intriguing but puzzling results. Messner et al ( 105 ) observed a distance decrease between IS/OS junction and RPE after the light stimulus. They observed that the OS tips and RPE were drawn closer together after light exposure, speculating that this might be associated with a decrease in volume of the SRS ( 105 ), which is conflicting with previous observations ( 99 ).…”
Section: Org Interpretations and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This framework is not meant to be exhaustive, but rather a starting point from which to move forward as a field. For example, methodological factors, such as lighting, 39,40 may influence retinal morphology. As such, standardization of lighting conditions may require standardization in the future, although whether this makes a significant difference in AD measurements remains to be systematically investigated.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This framework is not meant to be exhaustive, but rather a starting point from which to move forward as a field. For example, methodological factors, such as lighting,39,40 may influence retinal morphology. As such, standardization of lighting conditions may require standardization in the future, although whether this makes a significant difference in AD measurements remains to be systematically investigated.Looking to the future, use of this minimum data set could spur efficient data accumulation and analysis in the field, including data examining within subjects, longitudinal change in cognitive aging, and AD.…”
mentioning
confidence: 99%